ROBUST, ULTRAVIOLET-PROTECTED AMBIENT CONDITION HISTORY INDICATOR AND METHOD OF MAKING SAME (2013)
An optically readable ambient condition history indicator can have a substrate, an indicator agent on the substrate surface, and a transparent layer overlying the indicator agent. The indicator agent can be capable of changing appearance in response to exposure to an ambient condition and the transparent layer can be subject to exposure to environmental ultraviolet radiation. The indicator can also include a radiation-filtering adhesive layer overlying the indicator agent to secure the transparent layer to the indicator agent, which adhesive layer can include an adhesive and an ultraviolet radiation filter and can contact both the transparent layer and the indicator agent-bearing substrate. The radiation-filtering adhesive layer can protect the indicator agent from ultraviolet radiation transmitted through the transparent layer and provide a simple, robust construction that is easy to manufacture and resists delamination. The adhesive itself is also protected from ultraviolet radiation. A simplified manufacturing method is also disclosed.